Noble Gases in Solid Compounds Show a Rich Display of Chemistry With Enough Pressure - Miao, Maosheng (Frontiers in Chemistry, 2020)
In this review, we summarize the rapid progress of noble gas chemistry in solid compounds under high pressure. Thanks to the recent development of first principles crystal structure search methods, many new noble gas compounds have been predicted and some have been synthesized. Strikingly, almost all types of chemical roles and interactions are found or predicted in these high-pressure noble gas compounds, ranging from cationic and anionic noble gases to covalent bonds between noble gas atoms, and to hydrogen bond-like noble gas bonds. Besides, the recently discovered He insertion reactions reveal a unique chemical force that displays no local chemical bonding, providing examples that noble gas reaction can advance the frontier of chemistry at the very basic level.